Charisma X a film by Efi Xirou - Xenakis, Iannis 1922-2001 (Mode, 2010)
Charisma X follows the life of Iannis Xenakis from childhood through his final composition. Musicologist Makis Solomos guides audience through Xenakis' key periods and accomplishments interspersed with musical performances and comments from those who knew or worked with Xenakis
Ton Griechisch, Französisch, Englisch ; Untertitel Englisch, Französisch, Deutsch, Griechisch. - Originally recorded by Vox Documentaries in Greece, 2008. - Enth. Ausschnitte aus: Psappha, Naama, Keren, Charisma, Nomos Alpha, Oresteïa
Keywords: Film; DVD-Video